2013
DOI: 10.1088/0004-637x/778/2/163
|View full text |Cite
|
Sign up to set email alerts
|

THE ULTRALUMINOUS X-RAY SOURCES NGC 1313 X-1 AND X-2: A BROADBAND STUDY WITHNuSTARANDXMM-Newton

Abstract: We present the results of NuSTAR and XMM-Newton observations of the two ultraluminous X-ray sources: NGC 1313 X-1 and X-2. The combined spectral bandpass of the two satellites enables us to produce the first spectrum of X-1 between 0.3 and 30 keV, while X-2 is not significantly detected by NuSTAR above 10 keV. The NuSTAR data demonstrate that X-1 has a clear cutoff above 10 keV, whose presence was only marginally detectable with previous X-ray observations. This cutoff rules out the interpretation of X-1 as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
232
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(267 citation statements)
references
References 67 publications
34
232
1
Order By: Relevance
“…An extended hot halo is a characteristic feature of the best-studied eclipsing X-ray binary, the low-mass Galactic system EXO 0748−676 (Bonnet-Bidaud et al 2001). Soft X-ray residuals consistent with thermal-plasma emission (and/or absorption) have been reported in several other (non-eclipsing) ULXs such as NGC 5408 X-1 (Middleton et al 2014(Middleton et al , 2015bSutton et al 2015;Pinto et al 2016b), NGC 6946 X-1 (Middleton et al 2014), Ho II X-1 (Miyaji et al 2001;Dewangan et al 2004), NGC 4395 X-1 (Stobbart et al 2006), NGC 4559 X-1 ), NGC 7424 ULX-2 (Soria et al 2006), NGC 1313 X-1 (Bachetti et al 2013;Pinto et al 2016b), and Ho IX X-1 . The last two of those ULXs are hard ultraluminous sources, while all the others are classified as soft ultraluminous.…”
Section: Spectral Properties: Broadened Disks Comptonization and Thementioning
confidence: 72%
“…An extended hot halo is a characteristic feature of the best-studied eclipsing X-ray binary, the low-mass Galactic system EXO 0748−676 (Bonnet-Bidaud et al 2001). Soft X-ray residuals consistent with thermal-plasma emission (and/or absorption) have been reported in several other (non-eclipsing) ULXs such as NGC 5408 X-1 (Middleton et al 2014(Middleton et al , 2015bSutton et al 2015;Pinto et al 2016b), NGC 6946 X-1 (Middleton et al 2014), Ho II X-1 (Miyaji et al 2001;Dewangan et al 2004), NGC 4395 X-1 (Stobbart et al 2006), NGC 4559 X-1 ), NGC 7424 ULX-2 (Soria et al 2006), NGC 1313 X-1 (Bachetti et al 2013;Pinto et al 2016b), and Ho IX X-1 . The last two of those ULXs are hard ultraluminous sources, while all the others are classified as soft ultraluminous.…”
Section: Spectral Properties: Broadened Disks Comptonization and Thementioning
confidence: 72%
“…As these features are not commonly observed in Galactic XRBs, they imply a new spectral regime, which is usually referred to as the 'ultraluminous state' (Roberts 2007;Gladstone et al 2009), and may be associated with super-Eddington accretion. A few luminous ULXs have very recently been observed with NuSTAR, resulting in spectra which demonstrate that the highenergy curvature persists above 10 keV (Bachetti et al 2013;Walton et al 2013a;Rana et al 2015), confirming this result. The spectral curvature may arise either from Comptonization in a cold, optically thick corona lying above an accretion disc (e.g.…”
mentioning
confidence: 65%
“…This model has also been used to fit other ULX spectra (e.g. Foschini et al 2006;Vierdayanti et al 2006;Godet et al 2012;Bachetti et al 2013). The parameters of the slim disc fit are listed in Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…With sensitivity above 10 keV, recent observations with the Nuclear Spectroscopic Telescope Array (NuStar ) have confirmed a spectral cutoff in ULXs such as NGC 1313 X-1 (Bachetti et al 2013). Gladstone et al (2009) suggested that the high energy roll-over and soft spectral feature seen in many ULX spectra may correspond to a super-Eddington state of ac-cretion onto a stellar-mass BH (the 'ultraluminous' state).…”
Section: Introductionmentioning
confidence: 99%